2008
DOI: 10.1093/treephys/28.6.947
|View full text |Cite
|
Sign up to set email alerts
|

Ionic homeostasis and reactive oxygen species control in leaves and xylem sap of two poplars subjected to NaCl stress

Abstract: We investigated the effects of increasing soil NaCl concentration on intracellular compartmentalization of salt and on the activities of antioxidant enzymes (superoxide dismutase (SOD), ascorbic peroxidase (APX), catalase (CAT) and glutathione reductase (GR)) and their role in the regulation of reactive oxygen species (ROS; O(2)(-*) and H(2)O(2)) in leaves and xylem sap of salt-tolerant Populus euphratica Oliv. and salt-sensitive P. popularis cv. 35-44. Mesophyll cells of P. euphratica exhibited a high capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
103
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(110 citation statements)
references
References 50 publications
6
103
1
Order By: Relevance
“…and Cl -in cell wall relative to the cytoplasm implies the active extrusion of salts from the cytosol, in addition to ion sequestration in the vacuole. This pattern of salt compartmentation suggests a reduction of the toxic effects of salts in the cytoplasm, thus limiting the over production of ROS and avoiding secondary oxidative stress in leaf cells of P. euphratica (Wang et al , 2008. Leaf respiration markedly decreased in P. popularis, but not in P. euphratica, after 2 weeks of salt treatment (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…and Cl -in cell wall relative to the cytoplasm implies the active extrusion of salts from the cytosol, in addition to ion sequestration in the vacuole. This pattern of salt compartmentation suggests a reduction of the toxic effects of salts in the cytoplasm, thus limiting the over production of ROS and avoiding secondary oxidative stress in leaf cells of P. euphratica (Wang et al , 2008. Leaf respiration markedly decreased in P. popularis, but not in P. euphratica, after 2 weeks of salt treatment (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, by using confocal laser microscopy, they found ROS accumulation in the cytoplasm and mitochondria. The effect of salinity on ROS levels (O2 .− and H2O2) was also monitored in the xylem sap in two poplar cultivars with different levels of salt sensitivity [210]. After 18 days of treatment (250 mM NaCl) these authors only observed significant O2 .− and H2O2 accumulation in the NaCl-sensitive plants.…”
Section: Ros and Rns Generationmentioning
confidence: 99%
“…We found that salt-sensitive poplar species are usually unable to restrict the large accumulations of Na + and Cl -in root and shoot tissues, resulting in significant increases in ROS production despite marked increases in the activities of antioxidant enzymes in leaves and xylem sap. [4][5][6][7]27 As compared to salt-sensitive poplars, P. euphratica plants effectively restricted the salt accumulation and did not exhibit an oxidative burst in response to the NaCl treatments. 4,27 We hypothesized that salt-tolerant P. euphratica attenuates oxidative stress by NaCl exclusion, thus enabling ROS homeostasis to be maintained under saline conditions.…”
Section: Discussionmentioning
confidence: 97%
“…[4][5][6][7]27 As compared to salt-sensitive poplars, P. euphratica plants effectively restricted the salt accumulation and did not exhibit an oxidative burst in response to the NaCl treatments. 4,27 We hypothesized that salt-tolerant P. euphratica attenuates oxidative stress by NaCl exclusion, thus enabling ROS homeostasis to be maintained under saline conditions. 4 Generally, the less accumulated salts could occur for two possibilities: inhibition of uptake or enhancement of active extrusion.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation